Highly active antiretroviral therapy and left ventricular diastolic function in children with human immunodeficiency virus infection - Ni Made Ayu Agustini; Eka Gunawijaya; Ni Putu Venny Kartika Yantie; Ketut Dewi Kumara Wati; Komang Ayu Witarini; Hendra Santoso (Indonesian Pediatric Society, 2019)
Background In the past, cardiovascular involvement did not seem to be a common complication of HIV, but in recent years it has been described more frequently. With the advent of highly active antiretroviral therapy (HAART), the symptoms of cardiac disease has changed, as the number of HIV-infected patients with abnormal diastolic parameters has increased significantly, often presenting as symptomatic rather than asymptomatic. Objective To analyze for a possible correlation between HAART duration and left ventricular diastolic function in HIV-infected children. Methods This cross-sectional study was conducted from December 2016 to December 2017 at the Cardiology and Allergy-Immunology Division/Department of Child Health, Universitas Udayana Medical School/Sanglah Hospital, Denpasar, Bali. Subjects with HAART were collected using a consecutive sampling method. The following data were recorded for each subject: age, sex, current stage of HIV, CD4+ level, as well as HAART regimen and duration of use. Transthoracic echocardiography was performed for tissue doppler imaging (TDI) of diastolic function. Spearman’s test was used to analyze the strength of correlation based on normality test results. Results This study involved 53 subjects, 21 of whom had impaired diastolic function. There was no correlation between HAART duration and diastolic function in children with HIV infection (r= -0.03; P=0.82). Conclusion Diastolic dysfunction is found in children under HAART treatment, but there is no correlation between HAART treatment duration and diastolic dysfunction.